Revisiting investment costs for green steel: Capital expenditures, firm level impacts, and policy implications - Alexandra Hüttel; Judith Lehner (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
The transition of the steel sector to carbon neutrality requires significant investment. In this study, we aim to better understand the scale of investment required for a transition to hydrogen-based steelmaking and the ability of listed steelmakers to finance this investment. First, we analyze how capital expenditures are estimated in the academic literature and compare them with reported investment costs of green steel projects. Second, we focus on how a targeted transition to carbon neutrality would affect the balance sheet and leverage of listed steelmakers operating in the EU-27 and compare the required investments with the companies' past capital expenditures. The study concludes that capital expenditure may be underestimated in the academic literature and derives recommendations for referencing and contextualizing capital expenditure estimates. Based on the identified impacts at the company level, we conclude with a discussion of the capabilities of listed steel producers to achieve carbon-neutral production, also from an industrial policy perspective.
Keywords: G31; 32; L61; Q54; 55; 330; Steel; investment cost; capital expenditure; CAPEX; decarbonization